2015
DOI: 10.21608/jppp.2015.75441
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Two Tomato Cultivars to Infestation by Certain Insect Pests

Abstract: Experiments were carried out at tomato field at Qalyubyia Governorate, Egypt cultivated with two different cultivars to test its susceptibility to infestation with Bemisia tabaci (Gennadius); aphids {Aphis gossypii and Myzus persicae (Sülzer)}; Empoasca decipiens Paoli and Tuta absoluta (Meyrick) in addition to the seasonal abundance of these pests on the two cultivars in two successive summer seasons (2012 and 2013). Results indicated that B. tabaci and aphids had two peaks of abundance in May and June in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Low numbers of Empoasca decipiens in spring plantation. (Abdallah & Faraj, 2015) in Egypt revealed that B. tabaci recorded 2-3 peaks of abundance whereas leaf hopper had 1-2 peaks in summer plantations for seasons 2012&2013. (Abdallah & Faraj, 2015) indicated that densities of B. tabaci remained at a low level during the winter but increased steadily from February to March until migration into field crops in April.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Low numbers of Empoasca decipiens in spring plantation. (Abdallah & Faraj, 2015) in Egypt revealed that B. tabaci recorded 2-3 peaks of abundance whereas leaf hopper had 1-2 peaks in summer plantations for seasons 2012&2013. (Abdallah & Faraj, 2015) indicated that densities of B. tabaci remained at a low level during the winter but increased steadily from February to March until migration into field crops in April.…”
mentioning
confidence: 99%
“…(Abdallah & Faraj, 2015) in Egypt revealed that B. tabaci recorded 2-3 peaks of abundance whereas leaf hopper had 1-2 peaks in summer plantations for seasons 2012&2013. (Abdallah & Faraj, 2015) indicated that densities of B. tabaci remained at a low level during the winter but increased steadily from February to March until migration into field crops in April. Population fluctuation of white fly and leafhopper was somewhat similar (Rawat Scholar et al, 2020) as there was a non-significant positive correlation between maximum temperature and relative humidity of morning but minimum temperature showed a non-significant negative correlation and for Hopper population was a non-significant positive correlation with maximum temperature & relative humidity of morning and non-significant negative correlation with minimum temperature.…”
mentioning
confidence: 99%